Development and Validation of Indonesian Nursing Care Instruments for Patients with End-Stage Kidney Disease - Nauvila Fitrotul Aini; Nursalam Nursalam; Ika Yuni Widyawati (Media Keperawatan Indonesia, 2026)
End-stage kidney disease is a global health problem with a steadily increasing prevalence. Nurses need standardized nursing care instruments to improve care quality and contribute to overall health care improvement. This study aimed to develop an Indonesian nursing care instrument for patients with end-stage kidney disease. The study used a research and development design conducted in two stages. In the first stage, 101 medical records and 11 respondents were involved, while the second stage included 9 respondents. Samples were selected using purposive sampling. Validity and reliability were tested using the Item Content Validity Index (I-CVI) and Kuder–Richardson 20 (KR-20), and data were analyzed descriptively. The instrument was developed for 10 nursing diagnoses: hypervolemia, ineffective breathing pattern, impaired gas exchange, activity intolerance, anxiety, risk of electrolyte imbalance, risk of imbalanced nutrition, risk of falling, risk of ineffective renal perfusion, and readiness for enhanced nutrition. The instrument was aligned with Indonesian nursing standards, including SDKI, SLKI, and SIKI. By providing structured guidance for diagnoses, outcomes, and interventions, this instrument supports nurses in daily practice, improves documentation accuracy, and enhances consistency and quality of nursing care. Nurses’ evaluations indicated that the instrument is feasible for clinical implementation.